PRODUCTIVITY AND QUALITY OF SUGAR CONTENT, TOTAL ACID, PH, AND GANDARIA FRUIT WATER LEVELS (BOUEA MACROPHYLLA GRIIFF) IN DIFFERENT GEOGRAPHICAL CONDITIONS IN AMBON ISLAND (AN ANALYSIS OF MALUKU ENDEMIC PLANTS) - Pamella Mercy Papilaya (EDU SCIENCES JOURNAL, 2020)
Gandaria plant grows with tree habitus with a height of up to 27 m Spread of gandaria plants in Maluku, generally on Ambon Island and Saparua on Ambon Island, gandaria plants are spread from the coast to the hills. This study aims to determine the quality of sugar content, total acid, pH, water content and production of gandaria fruit (Bouea macrophylla Griff) in different geographical conditions on the island of Ambon using a purposive sampling method and laboratory analysis. The results showed that at an altitude of 0-400 asl with a production of 654 kg, 400-700 asl with a production of 681 kg and an altitude of 700-1100 asl producing 925 kg and the height of the place also affected the quality of gandaria with an average total sugar of 12.69%, content water 80.18%, acidity level 6.81% and pH 3. It was concluded that the higher the altitude of the place will affect the production and quality of gandaria fruit (Bouea macrophylla Griff).